2018
DOI: 10.5334/ijic.3954
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Shared Care in Cancer Survivors—A Systematic Review

Abstract: Objectives:To determine whether the shared care model during the follow-up of cancer survivors is effective in terms of patient-reported outcomes, clinical outcomes, and continuity of care.Methods:Using systematic review methods, studies were searched from six electronic databases—MEDLINE (n = 474), British Nursing Index (n = 320), CINAHL (n = 437), Cochrane Library (n = 370), HMIC (n = 77), and Social Care Online (n = 210). The review considered all health-related outcomes that evaluated the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 37 publications
2
76
0
4
Order By: Relevance
“…4 The findings of this study confirmed the advantage of involving oncologists and primary care physicians in patient care, which has been associated with positive outcomes during survivorship. 29 However, even in the publicly funded poorly understood, and implementation of efforts remains fragmented. 31 We suggest that such a model be tailored to address barriers, including funding constraints, staffing shortages, and lack of shared information systems between different health care sectors.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…4 The findings of this study confirmed the advantage of involving oncologists and primary care physicians in patient care, which has been associated with positive outcomes during survivorship. 29 However, even in the publicly funded poorly understood, and implementation of efforts remains fragmented. 31 We suggest that such a model be tailored to address barriers, including funding constraints, staffing shortages, and lack of shared information systems between different health care sectors.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…Overall, shared-care is highly acceptable, resulting in better patient compliance and satisfaction. In terms of effectiveness, shared-care has been shown to be similar to usual care ( 37 , 38 ). The current findings and recommendations of this study have implications for the integration of a shared-care model into routine primary care practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews have found equivalent quality of life, mental health and clinical outcomes for cancer survivors who follow-up in primary care and specialists services [ 8 ], with lower costs associated with shared care models [ 9 ]. It is also the preferred model of survivorship care by cancer survivors, general practitioners and specialists [ 10 ].…”
Section: Introductionmentioning
confidence: 99%